ZAKAT AS TAX REDUCTION: STUDY OF MUSLIM COMMUNITY PERCEPTION IN INDONESIA AND MALAYSIA - Ahmad Hafidh, Aula; Johari, Fuadah; Sholeh, Maimun; Suprayitno, Eko; Ngadiyono, Ngadiyono (Universitas Airlangga, 2021)
This study aims to examine the model adopted based on Muslim consumer perceptions of taxes through the zakat system. This research uses three stages of comprehensive technical analysis through demographic depiction of respondents based on distribution frequently, then tests the adopted factors using Exploratory Factor Analysis (EFA) to select and determine the number of factors and related items. In the final stage, data analysis is carried out in the form of the modeling technique using Structure Equations Model (SEM) to test the quality of the models and hypotheses produced. 152 respondents were collected who were sampled in this study, the majority of respondents are 77 Malaysian citizens and 75 Indonesian residents. At the testing stage of the model through the Structural Equation Model (SEM), based on the results of the formation factors in the test, it can be said that only the knowledge about tax, religious, and service variables have an impact on perception toward through zakat system positively and significantly, but through testing the serviceability of a model results in a determinant coefficient of 0.668, which it was relatively strong to explaining independent variable.